Analysis of Japanese Directive Speech Acts in the Anime Skip and Loafer - I Ketut Windra Yuda; I Kadek Antartika; Putu Dewi Merlyna Yuda Pramesti (Civiliza Publishing, Indonesia., 2026)
In pragmatic studies, speech is one of the studies that discusses the use of speech in a conversation. The purpose of this study is to analyze the meaning of directive speech acts, the forms of directive speech acts used, and social contextual factors that influence the selection of directive speech act forms used in the anime Skip and Loafer. This study employs a qualitative approach with a descriptive research design. The data collection method used is the observation method followed by note-taking. In analyzing the data, the study employs Namatame`s (1996) theory of the meaning of directive speech acts, Yule`s (1996) theory of speech act expressions, and Hymes`(1974) theory of speech acts. The results of the study indicate that 44 instances of directive speech acts were identified in the anime Skip and Loafer. From this data, six meaning of directive speech acts were identified: command, request, prohibition, permission, suggestion, and invitation. Based on the form of speech act expressions used, 37 instances of direct speech acts and 7 instances of indirect speech acts were found. Meanwhile, the social contextual factors that influence the selection of directive speech act expressions used in the anime Skip and Loafer include setting and scene, which indicate the formal nature of the situation and the location of the conversation; participants, which indicate the speaker`s role, differences in status, and relationship between the speaker and the addressee; and ends, which indicate the speaker`s intention or purpose in uttering the speech act.